Nutritional value and antimicrobial activity of selected edible tubers of Namibia (Namibian Journal for Research, Science and Technology, 2024)
Indigenous leafy vegetables have been extensively studied, but edible tuberous vegetables remain relatively underexplored in terms of their nutritional and medicinal value. This study aimed to evaluate the macronutrient, total phenolic and flavonoid contents, as well as the antioxidant, cytotoxicity, antimicrobial and antibiofilm activities, of six edible tubers from Namibia. Proximate analysis revealed that the tubers had high total carbohydrate and energy contents, with the highest values recorded for Walleria nutans. The high protein content of 13 g/100 g dry mass recorded for Coccinia rehmannii supports the use of members of this genus as nutritional protein supplements. The best, albeit weak, antimicrobial activity was recorded for the dichloromethane (DCM) extract of Eulophia hereroensis, with a minimum inhibitory concentration (MIC) of 2.5 mg/mL against Escherichia coli. Evaluation of the antibiofilm activity against Staphylococcus aureus showed that the DCM extract of Walleria nutans displayed the strongest biofilm formation inhibitory activity, whereas E. hereroensis exhibited the strongest biofilm eradication activity. A high total phenolic content and strong antioxidant activity were recorded for the aqueous methanolic extract of E. hereroensis, with IC₅₀ values of 0.056 ± 0.000 mg/mL and 0.041 ± 0.003 mg/mL obtained using the DPPH and H₂O₂ scavenging assays, respectively. All tubers showed little to no cytotoxicity, with CC₅₀ values > 200 µg/mL against the VERO cell line. The macronutrient content, in vitro antioxidant activity and antimicrobial activity of the selected tuberous vegetables are reported here for the first time. Eulophia hereroensis and W. nutans showed potential as functional foods and merit further in-depth phytochemical study to isolate and characterise the phenolic compounds and potential antibiofilm agents.
Keywords: Edible tubers; Proximate content; Antimicrobal; Antioxidant; Antibiofilm; Cytotoxicity